171 Inflatable Penile Prosthesis Infection Successfully Managed by Non-Operative Novel Treatment Strategies: A Case Report. (1st May 2022) - Goldstein, I.; Uloko, M.; Butera, M.; Cook, M.
ABSTRACT: Introduction: IPP infections occur in approximately 1% of cases. The fundamental principle for treatment has always been surgical removal of all components. Explantation/reimplantation surgery, however, may be unsuccessful, require additional surgeries, and/or result in poor patient satisfaction, reduced penile sensation, and decreased penile length. A patient presented 4 weeks post-op with an obvious IPP infection. Culture of scrotal drainage prior to antibiotic administration grew serratia marcescens, enterococcus faecalis, and citrobacter freundii. The patient was informed explanation was required, but he refused and requested we "do what we can" first. He was made aware of the lack of data supporting non-operative strategies for IPP infection. Objective: To present, likely for the first time, non-operative strategies including IV/oral antibiotics, low intensity shockwave therapy (LiSWT), and immune therapy can result in successful IPP infection treatment. Methods: A 49 yo with a 14 year history of ED underwent insertion of an 20 cm Titan IPP (Coloplast) with submuscular reservoir placement. Four weeks post-op he presented with fever (101°F), elevated WBC (15, 400), purulent drainage from a swollen, tender scrotum, and tenderness of all IPP components. We discussed non-operative management. He was admitted for broad spectrum IV antibiotics/antifungal agents: Vancomycin, Piperacillin and Tazobactam, and Fluconazole. After 6 days of IV antibiotics the patient became afebrile, WBC normalized (8, 000) but he developed mildly abnormal renal and liver function tests. He was discharged on oral Levofloxacin daily for 30 days. Grayscale ultrasound showed fluid around the pump and scrotal tubing with significant device tenderness and scrotal drainage through two small sinus tracts confirming persistent infection. We assessed the degree of purulent scrotal drainage on gauze kept on the scrotum for 10 hour periods. LiSWT (Urogold 100 MTS, parabolic unfocused probe OPP 155, energy flux density 0.13 mJ/mm 2, Hz 3.0, total shocks 6, 600/treatment) was administered to the device components and scrotum for two weeks daily, then twice weekly x 2 weeks and then weekly x 4 weeks. Concomitantly he received immune therapy via subcutaneous peptide administration and ozone blood dialysis twice weekly x2 weeks and then weekly x 4 weeks. Results: The patient progressively improved, remaining afebrile, with WBC (5, 000) and liver and renal function tests normalized at 1 week. Scrotal drainage stopped at 2 weeks and scrotal sinus tracts healed. There was no pain/tenderness of device components or scrotum at 2.5 weeks. There was no skin fixation to any device component. The patient could easily inflate/deflate the device to full rigidity/flaccidity without pain at 3 weeks and intercourse with orgasm at 5 weeks. Grayscale ultrasound at 4 weeks showed absent fluid around the device components. Conclusions: This is the first case report of successful management of an infected IPP using non-operative novel treatments. The effect of immune therapy is to enhance immune response to infection. Concerning the management of infection with LiSWT, it has been shown to have anti-infective properties, upregulate/recruit anti-bacterial/microbial peptide LL37, increase local blood flow, possibly inhibit biofilm, and result in salvage of infected breast and hip prostheses. Disclosure: Work supported by industry: no.